ACCESS TO THE INTERNET AS A SOCIAL RIGHT (Reflection and Critique Law Magazine, 2024)
ABSTRACTThe present article had as its theme to reflect on internet access as a fundamental right of the citizen, especially in the present conjuncture of technological expansion. In this context, the study aimed to analyze the importance of enacting the right of internet access to all Brazilians in the Constitutional Charter as a way of facilitating the realization of full enjoyment of citizenship in an indiscriminate way, considering that under the current prism, the quality of citizen it goes beyond political rights and citizenship is intrinsically related to the process of digital inclusion and, therefore, social inclusion. To carry out the study, a descriptive-analytical methodological approach was used, developed through bibliographic, documentary, qualitative research through information and documents on the subject. Thus, the result was the conviction that in a society where the use of digital technology of universal reach is a constant need, access to the internet as a social right is a way of guaranteeing openness to other fundamental rights. In view of this, it is necessary to affirm the Brazilian Constitutional Charter of internet access as a social right extended to all, as a way of removing the social injustices that may arise from the denial of this right, considering that in the face of new paradigms, access to the internet it is a fundamental element to promote equality, social justice and the full enjoyment of citizenship. Keywords: Fundamental Rights. Internet access. Positivity.